A zwitterionic polymer hydrogel and its preparation method and application

By using crosslinking technology of ureidimidazole azoheterocyclic carbene, zwitterionic monomer and amide compounds in the hydrogel, zwitterionic polymer hydrogel is formed, which solves the problem of poor mechanical properties of conductive hydrogels and achieves comprehensive performance of high tensile, self-healing and electrical conductivity.

CN116102688BActive Publication Date: 2025-03-04WUHAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210496451.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-09
Publication Date
2025-03-04
Estimated Expiration
2042-05-09

AI Technical Summary

Technical Problem

The existing conductive hydrogels have poor mechanical properties during repeated deformation or extrusion, resulting in loss of function and difficulty in meeting the complex strain environment. The traditional hydrogel network structure is uneven and lacks an energy dissipation mechanism, which leads to easy damage and fracture.

Method used

Ureadyimidazole-based anicyclic carbene, zwitterionic monomers and amide compounds are used to cross-link dynamic covalent bonds and non-covalent bonds to form zwitterionic polymer hydrogels, and use electrostatic action and hydrogen bonds to impart various properties such as stretchability and self-healing properties to the hydrogel.

Benefits of technology

The hydrogel is achieved with good tensile, adhesion, self-healing and conductivity. The maximum strain can reach 1100kPa, and the repair rate reaches 80%, which improves the mechanical strength and durability of the hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116102688B_ABST
    Figure CN116102688B_ABST
Patent Text Reader

Abstract

The invention discloses a zwitterionic polymer hydrogel, belonging to the technical field of hydrogels, wherein the zwitterionic polymer hydrogel is cross-linked by ureido imidazole nitrogen heterocyclic carbene, zwitterionic monomer, and amide compounds through dynamic covalent bonds and non-covalent bonds. The invention improves the mechanical strength of the hydrogel by constructing a more stable network structure, while increasing the adhesion of the material; and imparts stretchability and self-repairing properties to the hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a zwitterionic polymer hydrogel and a preparation method and application thereof, belonging to the technical field of hydrogels. Background Art

[0002] Conductive hydrogels, as typical soft and wet materials, have become excellent materials for preparing ionic skin strain sensors in recent decades due to their unique softness, biocompatibility and three-dimensional network structure. However, most hydrogels have poor mechanical properties when repeatedly deformed or squeezed, resulting in loss of gel function and difficulty in meeting complex strain environments. These factors severely limit the practical application of conductive hydrogels as strain sensors. Therefore, in order to continuously maintain the integrity of the network structure, the self-healing ability of the gel can be enhanced to repair damaged parts, thereby improving durability and reliability. On the other hand, during the deformation process, the response receiving ability of the conductive network to small external strains can be improved through the ionic conduction mechanism, thereby obtaining high sensing performance and high sensitivity.

[0003] Traditional hydrogels form three-dimensional networks by covalent crosslinking. However, there is a problem of uneven dispersion of covalent crosslinking points, which leads to uneven polymer network structures in the gel, making the gel easy to break and fracture on a macro scale. This hydrogel network also lacks an energy dissipation mechanism. When subjected to external stress, the energy at the crack cannot be effectively dissipated, and the crack will continue to spread until it breaks. In addition, dynamic hydrogen bonds contribute to the energy dissipation and network reconstruction of the hydrogel, while also providing the hydrogel with self-healing ability at room temperature. Ion transport gives the hydrogel certain conductivity and sensing properties, and the signal is stable, fast and repeatable. The material also has fatigue resistance and good biocompatibility. This strategy provides a simpler and faster strategy for preparing artificial hydrogels. In previous studies, in order to optimize the sum of these properties, it is usually necessary to add tedious and time-consuming manufacturing steps to the preparation process of polymer hydrogels, and even control specific reaction temperatures and reaction times to initiate free radical polymerization. Therefore, in the field of flexible electronics, it is a challenge to develop ionic skin devices with as many excellent properties as possible using a simple gel preparation strategy. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a zwitterionic polymer hydrogel and a preparation method and application thereof, wherein the polymer hydrogel has good stretchability, plasticity, adhesion, conductivity, and self-healing properties, and solves the problem that common hydrogels have a single performance and cannot meet the actual situation. The hydrogel is endowed with multiple properties such as stretchability and self-healing properties by utilizing the electrostatic effect and hydrogen bonding effect of urea imidazole nitrogen heterocyclic carbene precursors, and the preparation method of the hydrogel is simple.

[0005] A zwitterionic polymer hydrogel is formed by cross-linking urea imidazole nitrogen heterocyclic carbene, zwitterionic monomers and amide compounds through dynamic covalent bonds and non-covalent bonds.

[0006] Optionally, the non-covalent bonds include electrostatic and hydrogen bonds.

[0007] Optionally, the maximum strain of the zwitterionic polymer hydrogel can reach 1100 kPa.

[0008] Optionally, the maximum stress is 340 kPa.

[0009] The repair rate of the zwitterionic polymer hydrogel reached 80% after 24 hours.

[0010] Optionally, the urea imidazole nitrogen heterocyclic carbene is selected from at least one of a pincer urea imidazole nitrogen heterocyclic carbene and a linear urea imidazole nitrogen heterocyclic carbene.

[0011] Optionally, the zwitterionic monomer is a betaine-type amphoteric surfactant.

[0012] Optionally, the betaine-type amphoteric surfactant is selected from one of carboxylic acid betaine and sulfonyl betaine.

[0013] Optionally, the carboxylic acid betaine is selected from at least one of methacrylic acid carboxy betaine and acryloylethyl carboxy betaine.

[0014] Optionally, the sulfobetaine is selected from at least one of methacrylic acid sulfobetaine and acryloylethyl sulfobetaine.

[0015] By using methacryloylethyl sulfobetaine, a more stable network structure can be constructed, the mechanical strength of the hydrogel can be improved, and the adhesion of the material can be increased.

[0016] Optionally, the amide compound is selected from at least one of acrylamide and N-vinyl caprolactam.

[0017] According to yet another aspect of the present application, a preparation method is provided.

[0018] The method for preparing the zwitterionic polymer hydrogel described above comprises the following steps:

[0019] A mixture containing zwitterionic monomers, amide compounds, crosslinking agents, ureidoimidazole nitrogen heterocyclic carbenes and photoinitiators is subjected to a photoinitiated reaction to obtain the zwitterionic hydrogel.

[0020] Optionally, the cross-linking agent is selected from at least one of polyethylene glycol diacrylate and N,N′-methylenebisacrylamide.

[0021] Optionally, the photoinitiator is selected from aromatic ketone compounds.

[0022] Optionally, the aromatic ketone compound is selected from at least one of 2-hydroxy-2-methyl-1-phenylpropanone and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone.

[0023] Optionally, the molar ratio of the ureido imidazole nitrogen heterocyclic carbene, the zwitterionic monomer, and the amide compound is 1-3:1-3:1-3.

[0024] Optionally, the ureido imidazole nitrogen heterocyclic carbene is added in the form of an aqueous solution thereof, and the concentration of the ureido imidazole nitrogen heterocyclic carbene in the aqueous solution is 1 mol / L to 2 mol / L.

[0025] Optionally, the amount of the cross-linking agent used is 0.1% to 0.3% of the total molar amount of the zwitterionic monomer and the amide compound.

[0026] Optionally, the amount of the photoinitiator used is 0.1% to 0.3% of the total molar amount of the zwitterionic monomer and the ureidoimidazole nitrogen heterocyclic carbene.

[0027] Optionally, the conditions for the photoinitiated reaction are as follows:

[0028] The light source is ultraviolet light, and the wavelength of the ultraviolet light is 365 nm ~ 380 nm;

[0029] The reaction time is 20 nm ~30 min.

[0030] According to a third aspect of the present application, an application is provided.

[0031] Application of the zwitterionic polymer hydrogel described above and / or the zwitterionic polymer hydrogel obtained by the preparation method described above in flexible electronic devices, wearable devices, stretchable bioelectronic devices, electronic detection instrument patches, and medical adhesives.

[0032] The beneficial effects of this application include:

[0033] 1) The zwitterionic hydrogel provided in this application has good stretchability, adhesion, self-healing and other properties. The zwitterionic hydrogel has adhesion and can be used to prepare medical adhesives and other products; the hydrogel adhesion makes it closely contact with the skin, and then perfectly conducts signals through the conductive property. It can be used in flexible electronic devices, wearable devices, stretchable bioelectronic devices, and electronic detection instrument patches, and has a wide range of application prospects.

[0034] 2) The preparation method of zwitterionic polymer hydrogel provided in this application is a one-step method, which has the advantages of being simple, efficient and improving cross-linking uniformity. The electrostatic effect and hydrogen bonding effect of urea imidazole nitrogen heterocyclic carbene are used to give the hydrogel multiple properties such as stretchability and self-healing properties; betaine-type amphoteric surfactants (such as methyl methacryloylethyl sulfobetaine) can be used to construct a more stable network structure, improve the mechanical strength of the hydrogel, and increase the adhesion of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The mass spectrum of the ureido imidazole nitrogen heterocyclic carbene used in this application.

[0036] Figure 2 This is a diagram showing the self-healing performance of sample UL1-S3A3 according to the embodiment of the present application. DETAILED DESCRIPTION

[0037] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0038] It should be noted that the ureidoimidazole nitrogen heterocyclic carbene in this experiment was synthesized independently.

[0039] Synthesis process:

[0040] S1. Under nitrogen atmosphere, add dichloromethane and methylamine solution to the reaction bottle in sequence, then lower the temperature to about 0°C, slowly add 3-chloropropyl isocyanate, return to room temperature after addition, and stir to react for 24 hours. After the reaction is completed, remove the organic solvent by rotary evaporation under reduced pressure, and after the solvent is evaporated to dryness, wash the solid several times with ether to obtain the product.

[0041] S2. Under nitrogen atmosphere, add dichloromethane and 1-(3-aminopropyl)imidazole to the reaction bottle in sequence, then lower the temperature to about 0°C, slowly add allyl isocyanate, return to room temperature after addition, and stir to react for 24 hours. After the reaction is completed, remove the organic solvent by rotary evaporation under reduced pressure, and after the solvent is evaporated to dryness, wash the solid several times with ether to obtain the product.

[0042] S3. Add the products obtained from step 1 and step 2 into a round-bottom flask respectively, then add acetonitrile, and reflux and stir at 81°C for 24 hours. After the reaction is completed, perform rotary evaporation under reduced pressure, evaporate the solvent to dryness, and wet-load the column (dichloromethane: methanol = 40:1→1:1) to obtain the final product.

[0043] Other raw materials in the examples of this application were purchased through commercial channels, including:

[0044] Methacryloylethyl sulfobetaine (SBMA), AR>99% (Sinopharm Chemical Reagent Co., Ltd.).

[0045] Acrylamide (AM), analytical grade AR (Sinopharm Chemical Reagent Co., Ltd.).

[0046] Polyethylene glycol diacrylate (PEGDA), AR>99% (Shanghai Aladdin Biochemical Technology Co., Ltd.).

[0047] 2-Hydroxy-2-methyl-1-phenylpropanone, R>99% (Shanghai Aladdin Biochemical Technology Co., Ltd.).

[0048] The analysis method in the examples of this application is as follows:

[0049] Mass spectrometry analysis was performed using a Bruker DRX 400 MS spectrometer.

[0050] Tensile analysis was performed using a universal tensile machine.

[0051] The conductivity performance was analyzed using a digital four-probe tester (ST2258C, China).

[0052] The tensile strain is calculated as follows:

[0053]

[0054] Where L is the tensile length of the sample; L0 is the initial length of the sample.

[0055] The calculation method of fracture stress is as follows:

[0056]

[0057] Where F is the load N; A0 is the cross-sectional area of ​​the sample. Example 1

[0058] At room temperature, weigh 0.15g of ureido imidazole nitrogen heterocyclic carbene, add 4 ml of water to make a 1mol / L solution, 0.2g of SBMA, 0.3g of AM, 17 μL of polyethylene glycol diacrylate (accounting for 0.2% of the total monomer molar amount), 4 μL of 2-hydroxy-2-methyl-1-phenylacetone (accounting for 0.3% of the total monomer molar amount), place it in a clean 25 ml beaker, add a rotor and place it on a magnetic workbench and stir at a stirring speed of 1000 r / min for 20 min. The above mixed solution was injected into two 3*3 cm glass sandwich plates with a thickness of 2 mm between the glass plates using a 2 mL syringe. After the solution was injected, the small bubbles in the glass plate were emptied, and the glass plate was placed in a UV curing box with a wavelength of 365 nm for 30 minutes. After the temperature of the glass plate cooled to room temperature, the hydrogel was taken out, numbered as sample UL1-S2A3, and stored in a ziplock bag. Example 2

[0059] At room temperature, weigh 0.15g of ureido imidazole nitrogen heterocyclic carbene, add 4ml water to make a 1mol / L solution, 0.3g SBMA, 0.3g AM, 21μL polyethylene glycol diacrylate (accounting for 0.2% of the total monomer molar amount), 5μL 2-hydroxy-2-methyl-1-phenylpropanone (accounting for 0.3% of the total monomer molar amount), place it in a clean 25ml beaker, add a rotor and place it on a magnetic workbench at a stirring speed of 1000 r / min for 20 min. The above mixed solution was injected into two 3*3cm glass sandwich plates with a thickness of 2mm between the glass plates using a 2mL syringe. After the solution was injected, the small bubbles in the glass plate were emptied, and then the glass plate was placed in a UV curing box with a wavelength of 365nm for 30min. After the temperature of the glass plate cooled to room temperature, the hydrogel was taken out, numbered as sample UL1-S3A3, and stored in a ziplock bag. Example 3

[0060] At room temperature, weigh 0.15g of ureido imidazole nitrogen heterocyclic carbene, add 4ml water to make a 1mol / L solution, 0.4g SBMA, 0.3g AM, 25μL polyethylene glycol diacrylate (accounting for 0.2% of the total monomer molar amount), 6μL 2-hydroxy-2-methyl-1-phenylpropanone (accounting for 0.3% of the total monomer molar amount), place it in a clean 25ml beaker, add a rotor and place it on a magnetic workbench at a stirring speed of 1000 r / min for 20 min. The above mixed solution was injected into two 3*3cm glass sandwich plates with a thickness of 2mm between the glass plates using a 2mL syringe. After the solution was injected, the small bubbles in the glass plate were emptied, and the glass plate was placed in a UV curing box with a wavelength of 365nm for 30min. After the temperature of the glass plate cooled to room temperature, the hydrogel was taken out, numbered as sample UL1-S4A3, and stored in a ziplock bag. Example 4

[0061] The preparation process was the same as that in Example 1, except that the added masses of SBMA and AM were 0.3 g and 0.1 g, respectively. The obtained zwitterionic hydrogel was designated as sample UL1-S3A1. Example 5

[0062] The preparation process was the same as in Example 1, except that the added masses of SBMA and AM were 0.3 g and 0.15 g, respectively. The resulting zwitterionic hydrogel was designated as sample UL1-S3A. 1.5 . Example 6

[0063] The preparation process was the same as in Example 1, except that the added masses of SBMA and AM were 0.3 g and 0.25 g, respectively. The resulting zwitterionic hydrogel was designated as sample UL1-S3A. 2.5 .

[0064] Analysis Example 1 Uniaxial Tensile Test

[0065] The test method is as follows:

[0066] 1. Take a dumbbell-shaped sample of zwitterionic hydrogel with a length of 3 cm and a width of 0.1 cm, clamp 0.9 cm at each end, and leave 1.2 cm in the middle as the experimental area. Take the sample and perform uniaxial stretching on a universal tensile testing machine, and set the stretching speed to 50 mm / min.

[0067] The toughness of the hydrogel was calculated by the integrated area of ​​the stress-strain curve, and the elastic modulus was calculated by the initial slope of the stress-strain curve (strain in the range of 0%-20%).

[0068] The results of the tensile test show that as the SBMA content increases, the strain of the hydrogel increases, and the maximum strain can reach 1100%. As the AM content increases, the stress of the hydrogel increases, and the maximum can reach 340 kPa.

[0069] Analysis Example 2 Cyclic Uniaxial Tensile Test

[0070] The test method is as follows:

[0071] The hydrogels were subjected to a stretching cycle test at room temperature using the same universal stretching machine, and all hydrogel samples were cut into dumbbell-shaped specimens with a length, width, and thickness of 10 mm, 5 mm, and 1 mm, respectively. During the test, the maximum strain of the stretching cycle was set to 200%, the stretching speed was set to 100 mm / min, and the number of cycles was 10.

[0072] In addition, the dissipated energy of the hydrogel was calculated by the integrated area of ​​the stretching cycle curve, and the elastic modulus was calculated by the initial slope of the stretching cycle curve (strain in the range of 0%–20%).

[0073] Analysis Example 3 Self-repair performance test

[0074] The prepared S3A3 hydrogel was cut with a sharp blade, and the two halves of the hydrogel were brought into contact with each other with gentle force to promote the self-healing process. Finally, it was placed in an environment with a constant temperature of 37°C and a relative humidity of about 80%-90% for repair. Figure 2 This is a digital photo of the self-repaired hydrogel stained with methyl orange and brilliant green. The repaired hydrogel was subjected to a tensile test, such as Figure 2 After 24 hours, the repair efficiency reached 80%, which fully demonstrated its reliable self-healing performance. After the hydrogel was cut, the internal hydrogen bonds and electrostatic forces would be partially destroyed. When placed in a constant temperature and relatively humid environment, the polymer chains intertwined and entangled at the fracture, and the energy dissipation of the dynamic bonds enabled the hydrogel to spontaneously repair the damage.

[0075] Analysis Example 4 Conductive and Sensing Performance

[0076] The conductivity of the hydrogel was measured by a digital four-probe tester (ST2258C, China). The electrochemical properties of the hydrogel were measured using the four-electrode AC impedance method. The hydrogel was cut into samples with a length of 30 mm, a width of 10 mm, and a thickness of 1 mm. The conductivity (σS / cm) was calculated as follows: σ=L / (R*S), where L (cm) is the distance between the two probes, R (Ω) is the resistance of the hydrogel, and S (cm -2 ) is the cross-sectional area of ​​the hydrogel. The resistance change of the hydrogel was recorded by using an electrochemical analyzer / workstation (CHI600E, China). The resistance value was calculated according to Ohm's law (R = U / I). A constant voltage of 0.1 V was applied to the hydrogel, and the relative resistance change caused by different strains was expressed as GF = [(R-R0) / R0] / ε= (ΔR / R0) / ε, where R0 and R are the resistances of the original and stretched hydrogels, respectively, and ε is the strain of the hydrogel.

[0077] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A zwitterionic polymer hydrogel, characterized in that: The zwitterionic polymer hydrogel is formed by cross-linking urea imidazole nitrogen heterocyclic carbene, zwitterionic monomers, and amide compounds through dynamic covalent bonds and non-covalent bonds; The preparation method of the zwitterionic polymer hydrogel is: The zwitterionic monomer, amide compound, ureido imidazole nitrogen heterocyclic carbene, crosslinking agent and photoinitiator are mixed to carry out photoinitiation reaction to obtain the zwitterionic polymer hydrogel; The zwitterionic monomer is a betaine-type amphoteric surfactant, and the betaine-type amphoteric surfactant is selected from one of carboxylic betaine and sulfo betaine; the carboxylic betaine is selected from at least one of methacrylic acid carboxy betaine and acryloyl ethyl carboxy betaine; the sulfo betaine is selected from at least one of methacrylic acid sulfo betaine, acryloyl ethyl sulfo betaine and methacryloyl ethyl sulfo betaine; The amide compound is selected from at least one of acrylamide and N-vinyl caprolactam; The cross-linking agent is selected from at least one of polyethylene glycol diacrylate and N,N′-methylenebisacrylamide; The molar ratio of the ureido imidazole nitrogen heterocyclic carbene, the zwitterionic monomer, and the amide compound is 1-3:1-3:1-3; The synthesis process of ureido imidazole nitrogen heterocyclic carbene is as follows: S1. Under a nitrogen atmosphere, dichloromethane and methylamine solution were added to the reaction flask in sequence, and then the temperature was lowered to 0°C, and 3-chloropropyl isocyanate was slowly added. After the addition, the temperature was restored to room temperature and stirred for 24 hours. After the reaction was completed, the organic solvent was evaporated by rotary evaporation under reduced pressure. After the solvent was evaporated to dryness, the solid was washed several times with ether to obtain the product; S2. Under a nitrogen atmosphere, dichloromethane and 1-(3-aminopropyl)imidazole were added to the reaction flask in sequence, and then the temperature was lowered to 0°C, and allyl isocyanate was slowly added. After the addition, the temperature was restored to room temperature and stirred for 24 hours. After the reaction was completed, the organic solvent was evaporated by rotary evaporation under reduced pressure. After the solvent was evaporated to dryness, the solid was washed several times with ether to obtain the product. S3. Add the products obtained in step 1 and step 2 into a round-bottom flask respectively, then add acetonitrile, reflux and stir at 81°C for 24 hours; after the reaction is completed, perform rotary evaporation under reduced pressure, evaporate the solvent to dryness, and wet-load the sample through a column to obtain the final product.

2. A zwitterionic polymer hydrogel according to claim 1, characterized in that: The non-covalent bonds include electrostatic and hydrogen bonds; the maximum strain of the zwitterionic polymer hydrogel is 1100%; and the maximum stress is 340 kPa.

3. A zwitterionic polymer hydrogel according to claim 1, characterized in that: The photoinitiator is selected from aromatic ketone compounds; the aromatic ketone compounds are selected from at least one of 2-hydroxy-2-methyl-1-phenylpropanone and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone.

4. The zwitterionic polymer hydrogel according to claim 1, characterized in that: The urea imidazole nitrogen heterocyclic carbene is added in the form of its aqueous solution, and the concentration of the aqueous solution is 1 mol / L to 2 mol / L; the amount of the cross-linking agent is 0.1% to 0.3% of the total molar amount of the zwitterionic monomer and the amide compound; the amount of the photoinitiator is 0.1% to 0.3% of the total molar amount of the zwitterionic monomer and the urea imidazole nitrogen heterocyclic carbene; the conditions of the photoinitiation reaction are as follows: the light source is ultraviolet light, and the wavelength of the ultraviolet light is 365nm to 380nm; the photoinitiation reaction time is controlled to be 20min to 30min.

5. A use of the zwitterionic polymer hydrogel according to any one of claims 1 to 4, characterized in that: Applications in flexible electronic devices, wearable devices, stretchable bioelectronic devices, electronic testing instrument adhesive sheets, and medical adhesives.

Citation Information

Patent Citations

  • Quick self-repairing betaine type zwitterionic polymer hydrogel and preparation method thereof

    CN111040196A

  • High-transparency self-repairing self-adhesion conductive elastic material and preparation method thereof

    CN114262403A